(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores the phenomenon of phoneme alteration, a natural linguistic process where the smallest units of sound in speech undergo changes due to various factors. The piece outlines several types of phoneme alterations, including assimilation, elision, metathesis, insertion, and flapping, explaining how each occurs in spoken language to facilitate easier articulation or reflect regional and social variations. The article further delves into the causes of these alterations, such as ease of pronunciation, language contact, dialect variation, and historical language changes. It also examines the impact of phoneme alterations on language evolution, dialect development, and language learning. This comprehensive overview provides readers with an understanding of the role phoneme alterations play in shaping the way languages develop and how they reflect the adaptability of human communication.